The Legal Framework in Addressing Modern Slavery and Human Trafficking a Focus on Indonesia - Harsya, Rabith Madah Khulaili; Zuwanda, Zulkham Sadat (The Easta Journal Law and Human Rights, 2024)
The legal, sociological, and practical aspects of stopping human trafficking and modern slavery in Indonesia are examined in this study. The study uses a mixed-methods approach, combining in-depth interviews with key informants from several sectors participating in anti-trafficking operations with normative analysis. The interviews provide rich insights from legal experts, law enforcement authorities, government representatives, NGOs, judicial staff, journalists, international organizations, and social workers; the normative analysis highlights the advantages and disadvantages of Indonesia's legal system. The results highlight difficulties such as a lack of resources, problems with coordination, and socioeconomic variables that increase susceptibility. Regular evaluations of the legal framework, improved coordination, victim-centric strategies, responsible media coverage, and international cooperation are among the recommendations. This study adds to the larger conversation about preventing human trafficking by providing a thorough grasp of the complex issues and viable solutions in the Indonesian setting.